2015
DOI: 10.1371/journal.pone.0132047
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of Multiple Endothelial Dysfunction Biomarkers with Chronic Kidney Disease

Abstract: The interrelationship of multiple endothelial biomarkers and chronic kidney disease (CKD) has not been well studied. We measured asymmetric dimethylarginine (ADMA), L-arginine, soluble intercellular adhesion molecule-1 (sICAM-1), soluble vascular adhesion molecule-1 (sVCAM-1), soluble E-selectin (sE-selectin), von Willebrand factor (vWF), flow-mediated dilation (FMD), and nitroglycerin-induced dilation (NID) in 201 patients with CKD and 201 community-based controls without CKD. Multivariable analyses were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…We decided a priori to adjust for potential confounders (age, sex, comorbidities, and SAPS II) that most likely affect disease severity and mortality. It has previously been shown that kidney function has an impact on the nitrite, l -arginine, and ADMA levels in plasma ( 32 ), and this is confirmed in this study because there was a significant correlation between the biomarker levels and the creatinine levels. An adjustment for this was done as urine output and blood urea nitrogen levels are included in the SAPS II.…”
Section: Discussionsupporting
confidence: 88%
“…We decided a priori to adjust for potential confounders (age, sex, comorbidities, and SAPS II) that most likely affect disease severity and mortality. It has previously been shown that kidney function has an impact on the nitrite, l -arginine, and ADMA levels in plasma ( 32 ), and this is confirmed in this study because there was a significant correlation between the biomarker levels and the creatinine levels. An adjustment for this was done as urine output and blood urea nitrogen levels are included in the SAPS II.…”
Section: Discussionsupporting
confidence: 88%
“…Besides, reduced vascular NO availability in this setting has been described in association with enhanced generation of oxygen free radicals by NADPH oxidases [ 9 , 10 ]. In addition, other factors including increased concentrations of the NOS inhibitor asymmetric dimethylarginine (ADMA) can contribute to endothelial dysfunction during renal failure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, UA has been shown to promote proliferation of vascular smooth muscle cells and reduce nitric oxide, resulting in endothelial dysfunction [ 19 ]. On the other hand, Chen et al [ 20 ] reported an interrelationship between multiple markers and pathways, leading to impaired endothelial function in patients with CKD. Given these relationships, there seems to be a pathological triangle between hyperuricemia, CKD, and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%